2016
DOI: 10.1038/srep39075
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome has a protective effect against oxazolone-induced colitis: a possible role in ulcerative colitis

Abstract: The inflammasomes induce maturation of pro-interleukin-1β (IL-1β) and pro-IL-18. We investigated roles of the NLRP3 inflammasome in the pathogenesis of ulcerative colitis (UC). After induction of oxazolone-induced colitis, a mouse UC model, colonic tissues were assayed for inflammatory mediators. Histological studies were performed on inflamed colonic tissue from mice and UC patients. Histological severity of murine colitis peaked on day 1, accompanied by an increase in the expression of Th2 cytokines includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 40 publications
(48 reference statements)
7
67
0
Order By: Relevance
“…Lu et al [11] reported that the frequency of IL-4 + CD4 + T cells was increased in UC patients. Itani et al [12] found that a biased Th2 response was induced in mice with colitis. Our previous studies also found that Th2 polarization in UC patients could be alleviated by specific immunotherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [11] reported that the frequency of IL-4 + CD4 + T cells was increased in UC patients. Itani et al [12] found that a biased Th2 response was induced in mice with colitis. Our previous studies also found that Th2 polarization in UC patients could be alleviated by specific immunotherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…In China, colon cancer is the third most common cancer and ranks fifth for its mortality rate (19). The average age for a patient with colon cancer is ~40 years, with being between 50 and 60 years, 10 years less compared with the average age of Western countries (19).…”
Section: Discussionmentioning
confidence: 99%
“…63,[69][70][71] As the NLRP3 inflammasome assembles in response to a vast range of DAMPs, it is likely that it senses a common cellular distress signal induced by these molecules, activation is also protective in colitis induced by another hapten, oxazolone, in a manner dependent on the production of both IL-1β and IL-18 production. 79 In contrast to these studies, other studies have reported protection from DSS or TNBS-induced colitis or AOM-DSS-induced CAC in mice deficient in the NLRP3 inflammasome components or IL-18 signaling. [80][81][82][83][84] The discrepancies in the phenotypes observed by different groups could be due to differences in microbial composition in different animal facilities, precise genetic backgrounds of the knockout mice, and experimental protocols.…”
Section: Nlrp3mentioning
confidence: 98%
“…NLRP3 also contributes to control of metastatic growth of colon cancer in the liver by promoting IL‐18‐mediated tumoricidal activity of NK cells . NLRP3 activation is also protective in colitis induced by another hapten, oxazolone, in a manner dependent on the production of both IL‐1β and IL‐18 production …”
Section: Inflammasomes In Intestinal Pathologies: Implications For Pymentioning
confidence: 99%